2010
DOI: 10.1002/ange.200905181
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Sintering on H‐ZSM‐5 Followed by Chemometrics of CO Adsorption and 2D Pressure‐Jump IR Spectroscopy of Adsorbed Species

Abstract: Zwei Welten: 2D‐IR‐Drucksprung‐Spektroskopie von adsorbiertem CO lieferte Informationen über die Umgebung und Lage von Platin‐Nanopartikeln auf Zeolith‐Trägern und das Verhalten der Pt‐Atome nach thermischer Behandlung (Aktivierung, katalytische Reaktion, Sinterung). In den Mesoporen und auf der äußeren Oberfläche des Trägers werden unterschiedliche Arten von Sintermechanismen beobachtet (siehe Bild; HF/LF=Hoch‐ bzw. Tieffrequenz).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…EXAFS is not sensitive to the minority phases (<10 %) and HAADF‐STEM imaging is a local technique. In prior studies on Pt‐ and Pd‐loaded (0.4–1 wt %) ZSM‐5, the IR spectra of room temperature adsorbed CO always indicated the presence of Pt and Pd nanoparticles as a consequence of metal agglomeration …”
Section: Figurementioning
confidence: 95%
See 2 more Smart Citations
“…EXAFS is not sensitive to the minority phases (<10 %) and HAADF‐STEM imaging is a local technique. In prior studies on Pt‐ and Pd‐loaded (0.4–1 wt %) ZSM‐5, the IR spectra of room temperature adsorbed CO always indicated the presence of Pt and Pd nanoparticles as a consequence of metal agglomeration …”
Section: Figurementioning
confidence: 95%
“…Today, there is a great interest to produce small‐pore zeolites loaded with atomically dispersed Pt and Pd at levels higher than 0.3 wt %. However, methods of loading transition metals ionically into SSZ‐13 at practically relevant levels (>1 wt %) are not known . Molliner et al.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…23 In this study, by combination of the CO titration and TEM results, it is also observed that 48%~56% of the Pt species in PtUSY exist in the form of "inner" particles (Please refer to the Supporting Information for details), which will be restricted to the micropore diameter and have small particle sizes (< 1 nm). 28 After the hydrothermal ageing, metallic Pt peaks arise on all the XRD patterns of the catalysts ( Fig. S1).…”
Section: Solid Propertiesmentioning
confidence: 98%
“…[16][17][18][19][20] Furthermore, the supported Pt particles may experience significant sintering and hereby deactivation during thermal ageing, especially in an oxidizing atmosphere like the automobile exhaust. 6,22,[25][26][27][28] However, the hydrothermal stability of Pt/zeolites as catalysts for soot oxidation has not been specifically studied so far. 22,23 Therefore, it is necessary to examine the durability of Pt/zeolites as soot oxidation catalysts to fully evaluate their application potential.…”
Section: Introductionmentioning
confidence: 99%